Marketing Management DIII Students' Distance Education Effectiveness For Citizens With Special Needs - Rahma Nur Praptiwi; Maria Nino Istia; Kristin Lukitaningrum (Eduvest - Journal of Universal Studies, 2021)
The existence of individuals with developmental and sensory disabilities (DIII MP-WNBK students) at the Jakarta State Polytechnic is a concern, especially when it is observed how they interact, the way they receive and attend lectures in class. So the situation that is completely online like this, becomes a challenge for them. The purpose of this study is to examine the effectiveness of distance education for MP-WNBK DIII students, and to explain efforts to improve their skills in accessing online lectures through the elearning.pnj.ac.id platform. This study uses an intervention method with a quantitative approach. The design of this research is a cross sectional study. The sample in this study was PS DIII MP-WNBK PNJ students. The number of samples taken as many as 76 students from a population of 92 students. The results of this study conclude that both lecturers and students enjoy using e-learning as a learning medium during distance learning. Learning with a high level of interaction is fun for both lecturers and students because it approaches face-to-face learning. Almost all students are able to use e-learning. E-learning is quite effective for distance learning.